مساز التصحيح في بيان الفصيح عند لغوني العراق في استدراك الصحيح على الصحيح - أمين, م. م. سوران علي محمد; رستم, م. م. هوز عمر (Sulaimani Journal for Humanities, 2023)
This study aims to show the features of the linguistic correction movement among the modern Iraqi linguists, its schools, its most prominent personalities and its authors despite the abundance of part of the general what has been written about it, with a focus on correcting the correction linguistic correction movement, and explaining the reasons for the decline in the impact of correction in language evaluation and the functioning of the public and private by following The inductive descriptive approach is fully consistent with the subject of the study.